2016
DOI: 10.1186/s13046-016-0308-0
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 overexpression is involved in cell proliferation and biochemical recurrence in prostate cancer after radical prostatectomy

Abstract: BackgroundBiochemical recurrence (BCR) is widely used to define the treatment success and to make decisions on if or how to initiate a secondary therapy, but uniform criteria to define BCR after radical prostatectomy (RP) is not yet completely assessed. UHRF1 has a unique function in regulating the epigenome by linking DNA methylation with histone marks. The clinical value of UHRF1 in PCa has not been well done. Therefore, we evaluated the prognostic significance of UHRF1.MethodUHRF1 expression in PCa cells wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 38 publications
(31 reference statements)
1
39
0
Order By: Relevance
“…Mean biochemical recurrence (BCR) free time in UHRF1-positive patients was around 23.0 months versus 38.9 months in UHRF1-negative patients while 5-year BCR-free survival rate was 12.4% in UHRF1-positive patients as compared with 51.8% in UHRF1-negative patients. These results support UHRF1 as a valuable independent prognostic factor to predict prostate cancer outcome after radical prostatectomy [ 109 ].…”
Section: Uhrf1 Expression In Different Cancerssupporting
confidence: 62%
See 3 more Smart Citations
“…Mean biochemical recurrence (BCR) free time in UHRF1-positive patients was around 23.0 months versus 38.9 months in UHRF1-negative patients while 5-year BCR-free survival rate was 12.4% in UHRF1-positive patients as compared with 51.8% in UHRF1-negative patients. These results support UHRF1 as a valuable independent prognostic factor to predict prostate cancer outcome after radical prostatectomy [ 109 ].…”
Section: Uhrf1 Expression In Different Cancerssupporting
confidence: 62%
“…This overexpression correlated with poor clinical prognosis as patients with high expression of UHRF1 had reduced median survival rates (10.4 years) as compared to patients with low expression of UHRF1 (12.4 years) [ 108 ]. Recently Wan et al reported similar results after analyzing expression of UHRF1 in 225 prostate cancer specimens [ 109 ]. UHRF1 staining was found in 47.1% of specimens which positively correlated with the Gleason score and the pathological stage of the disease [ 109 ].…”
Section: Uhrf1 Expression In Different Cancersmentioning
confidence: 62%
See 2 more Smart Citations
“…Currently, with the use of prostate-specific antigen (PSA) and prostate biopsy for prostate cancer screening, more and more patients can be diagnosed in the early stage and treated by radical prostatectomy [ 3 , 4 ]. However, about 25–50% of prostate cancer patients will have tumor recurrence after surgery, and many will die of the cancer [ 5 , 6 ]. Although current clinicopathological features such as Gleason score, disease stage, and PSA level provide important information, they do not accurately predict an individual patient’s prognosis, and new biomarkers are needed for prognostication [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%